2015
DOI: 10.35790/ebm.3.1.2015.6638
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMBERIAN EKSTRAK KUNYIT TERHADAP GAMBARAN HISTOPATOLOGI AORTA TIKUS WISTAR (rattus novergicus) HIPERLIPIDEMIA

Abstract: Atherosclerosis is a chronic inflammatory process that can be triggered by one of the risk factors of hyperlipidemia. This research was conducted to see the aorta associated with the provision of margarine that induce hyperlipidemia and administration of curcumin turmeric-containing compounds that act as antioxidants and anti-inflammatory. This research is experimental. The purpose of this study to determine the effect of extract of turmericon Wistar rat aorta histopathology induced hyperlipidemia with margari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…The results of this study indicated that a significant increase in the number of foam cells was found in the negative control group, atherosclerosis occurs in rats after a high-fat diet for 30 days (Loho & Lintong, 2015). The large number of foam cells is an early sign and pathognomonic of an atherosclerotic state.…”
Section: Discussionmentioning
confidence: 56%
“…The results of this study indicated that a significant increase in the number of foam cells was found in the negative control group, atherosclerosis occurs in rats after a high-fat diet for 30 days (Loho & Lintong, 2015). The large number of foam cells is an early sign and pathognomonic of an atherosclerotic state.…”
Section: Discussionmentioning
confidence: 56%
“…The research was conducted by giving a high-fat diet in the form of duck egg yolks and margarine. According to research by [36][37] white rats that were given 2 g duck egg yolk per day for 28 days and 5 gram of margarine per day for 28 days experienced a resulting increase in total cholesterol and triglyceride levels and microscopically visible intima foam cells and aortic media [36][37]. Hyperlipidemia conditions can cause endothelial dysfunction so that LDL can more easily enter the walls of blood vessels and can increase the production of oxygen free radicals and can cause LDL to be oxidized to LDL-ox.…”
Section: Microscopic Observation Results Of Aorta Of Atherosclerotic ...mentioning
confidence: 99%
“…The accumulation of LDL on blood vessel walls could be cell foam. 2 The high fatty diet was the food which compounds fat, and it can make the stress oxidation inside of the body. 2 Stress oxidative caused by free radical which binding with another compound to make a stable compound and could destroy another macromolecule, like the cell membrane of lipid, DNA and protein.…”
Section: Introductionmentioning
confidence: 99%
“…2 The high fatty diet was the food which compounds fat, and it can make the stress oxidation inside of the body. 2 Stress oxidative caused by free radical which binding with another compound to make a stable compound and could destroy another macromolecule, like the cell membrane of lipid, DNA and protein. 3 It could increase blood lipid, which is cholesterol and triglyceride level, which called hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%